Hybrid fluorescence-AFM explores articular surface degeneration in early osteoarthritis across length scales. (May 2021) - Tschaikowsky, Mathaeus; Neumann, Tanja; Brander, Sofia; Haschke, Heiko; Rolauffs, Bernd; Balzer, Bizan N.; Hugel, Thorsten
Abstract: Atomic force microscopy (AFM) has become a powerful tool for the characterization of materials at the nanoscale. Nevertheless, its application to hierarchical biological tissue like cartilage is still limited. One reason is that such samples are usually millimeters in size, while the AFM delivers much more localized information. Here a combination of AFM and fluorescence microscopy is presented where features on a millimeter sized tissue sample are selected by fluorescence microscopy on the micrometer scale and then mapped down to nanometer precision by AFM under native conditions. This served us to show that local changes in the organization of fluorescent stained cells, a marker for early osteoarthritis, correlate with a significant local reduction of the elastic modulus, local thinning of the collagen fibers, and a roughening of the articular surface. This approach is not only relevant for cartilage, but in general for the characterization of native biological tissue from the macro- to the nanoscale. Statement of Significance: Different length scales have to be studied to understand the function and dysfunction of hierarchically organized biomaterials or tissues. Here we combine a highly stable AFM with fluorescence microscopy and precisely motorized movement to correlate micro- and nanoscopic properties of articular cartilage on a millimeter sized sample under native conditions. This is necessary for unraveling the relationship between microscale organization of chondrocytes, micrometer scale changes in articular cartilage properties and nanoscale organization of collagen (including D-banding). We anticipate that such studies pave the way for a guided design of hierarchical biomaterials. Graphical abstract: Image, graphical abstract